IMPLEMENTATION OF BUSINESS COMMUNICATION IN GAY DRAMATURGY - Novi Andayani Praptiningsih (Universitas Muhammadiyah Jakarta, 2019)
The existence of gays in Indonesia as a cultured country is difficult to get support from various parties, because the cultural orientation adopted is eastern culture that strongly upholds religious values, norms, morals, and cus- toms. Not all gays are brave and able to do self-disclosure (coming out). Gay coming out and not fully coming out in Jakarta presents themselves as person's efforts to create specific impressions in front of others through the front and the backstage dramaturgy. The aim of the research was to find out the dramaturgical process and model in presenting themselves on the front stage and the back stage of both gay coming out and gay not fully coming out in Jakarta. The research method uses an interpretive paradigm with a subjective approach, with a type of qual- itative research. Data collection techniques using in-depth interviews, observation, FGD, and document review. Data analysis techniques apply interactive models of Miles Huberman.The results showed that Jakarta's gay self presentation on the front stage that had been fully coming out would do self-promotion tactics and even exagger- ate. But in gays who are not fully coming out, they will disclaimer by trying to deny and hide their identity as gay. But on the back stage, gays who have been or have not been fully coming out, both carry out a self promo- tion strategy as a technique of presenting themselves by opening themselves, especially in the gay community. Gay openness in coming out on family, community, and society is preceded by the coming in process, namely the acceptance of himself as gay. Business communication occurs when a gay person interacts with other gays, where the initial meeting is intended for friendship, developing into friendship. And then it can be a lover's relationship or a commercial relationship. This commercial relationship based on business is characterized by cash transac- tions and cash transfers, referred to as